Evaluation Transmission viruses Tomato mosaic virus (ToMV) by Soil on Nineveha Governorate / Iraq - Mheedi, Raghad Naif; Kassem, Nabil Aziz (Journal of Kerbala for Agricultural Sciences, 2018)
The aim of This study was to evolution transmission of viral isolates brought from tomato fields in Ninewah governorate in 2011 season showed the symptoms of the severe mosaic with green and yellow colors, the deformation of tomato leaves and moderate mosaic symptoms with slight yellowing the veins accompanied by mottle tomato plant, the Tomato mosaic virus (ToMV), isolates were diagnosed using DAS-ELISA (Double antibody sandwich - ELISA) .